Afazja jako zaburzenie mowy po urazie mózgu – studium przypadku - Lewicka, Tatiana (Logopedia Silesiana, 2012)
Speech disorder after brain damages in aphasia – case studyCranial-cerebral traumas are a serious sociomedical issue. Brain damages, caused by experiencedinjury, often lead to various kinesthetic deficits, as well as to cognitive and language disorders.Due to the damage of a nervous system, there are many deep speech disorders such as aphasia, mainlysenso-motorical type. The right evaluation of the appearing deficits, the right definition of therapeuticalobjectives and implementing of the therapy can give brain trauma patients the chance to regain thepossibility to communicate.